Mastering iOS development : location services - Welch, Keith (2014)
"In this Mastering iOS Development - Location Services training course, expert author Keith Welch demonstrates and explains how to work with iOS 8 location services for the iPhone and iPad. This course assumes you already have experience working with Xcode and building iOS apps. You will start out by learning the different options for mapping locations and how to get the user's current location. You will learn about displaying a map and creating a map that zooms. Keith will teach you how to provide turn-by-turn directions, calculate the distance, and switch from road to satellite views. Finally, this video tutorial will teach you how to create reminders and location based reminders. "--Resource description page.